Interleukin‐33 predicts poor prognosis and promotes ovarian cancer cell growth and metastasis through regulating ERK and JNK signaling pathways. Issue 1 (9th September 2015) - Tong, Xiaoguang; Barbour, Mark; Hou, Kezuo; Gao, Chao; Cao, Shuang; Zheng, Jingli; Zhao, Yang; Mu, Rong; Jiang, Hui-Rong
Abstract : Epithelial ovarian cancer (EOC) is the most lethal gynecological cancer, it remains a huge challenge to understand the cellular and molecular mechanisms of the aggressive behavior of EOC cells. Here we investigated the role of an immunomodulatory cytokine IL‐33 and its receptor ST2 in mediating the growth and metastasis of EOC. Our data show that both IL‐33 and ST2 were highly up‐regulated in EOC tumors compared with normal ovary and ovarian benign tumors, and the expression levels were further increased in tumor tissues at the metastatic site. The expression levels of IL‐33 and ST2 were positively correlated with the Ki‐67 expression, and negatively correlated with the patient survival time. Using EOC cell lines, we observed that cells knocked down of IL‐33 gene by siRNA had reduced migratory and invasive potential, while full length human IL‐33 (fl‐hIL‐33) promoted the invasive, migratory and proliferative capacity of EOC cells and this process could be inhibited by IL‐33 decoy receptor sST2. Signaling pathway analysis suggested that IL‐33 increased the phosphorylation of ERK and JNK which was blocked by sST2. Fl‐hIL‐33‐induced increases in EOC cell migration, invasive potential and proliferation were specifically abrogated by treatment with the ERK inhibitor U0126 while JNK inhibitor SP600125 only disrupted IL‐33‐induced enhancement of cell viability. Taken together, our data suggest that IL‐33/ST2 axis closely associates with poor prognosis of EOC patients, and it promotes ovarian cancer growth and metastasis through regulating ERK and JNK signaling pathways. Thus IL‐33/ST2 might be potential prognosis markers and therapeutic targets for EOC patients. Highlights: Increased IL‐33/ST2 expression in EOC tumors, particularly EOC metastatic tumors. Expression levels of IL‐33/ST2 negatively correlate with patient survival time. Fl‐hIL‐33 promotes the invasive, migratory and proliferative capacity of EOC cells. Fl‐hIL‐33 promotes ECO growth and metastasis through ERK and JNK signaling pathways.